Structural and functional studies of pseudomurein peptide ligases in methanogenic archaea : a dissertation presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Biochemistry, Massey University, Manawatu, New Zealand - Subedi, Bishwa Prakash (Massey University, 2018)
Prokaryotes are classified as Archaea and Bacteria in the tree of life and have several distinguishing characteristics, among which the cell wall is one of the most essential and early evolving. Cell walls serve a number of essential functions including protection against osmotic stress, maintenance of cell shape, reduction of lateral gene transfer, and protection from viruses. The cell walls in Bacteria are predominantly comprised of peptidoglycan (murein) whereas Archaea contain a wide range of cell wall types, none of them being murein. However, methanogens of the order Methanobacteriales and Methanopyrales contain pseudomurein that shares an overall architectural structure similar to that of murein with a glycan backbone that is cross-linked by a peptide. Understanding the enzymatic steps for pseudomurein pentapeptide biosynthesis and structural information of these enzymes, could be key to resolving the evolutionary history of cell wall synthesis and was the focus of this project. Analysis of the sequences and gene clusters of the murein peptide ligase genes suggested that analogous putative pseudomurein peptide ligases exist in methanogens. Moreover, the structures of two pseudomurein peptide ligases, pMurE and pMurC, the first of any archaeal peptide ligase, have been determined and their structural homology with bacterial murein ligase MurE and MurC, respectively, was analysed. The structures of pMurE from Methanothermus fervidus DSM 2088 (Mfer762) and Methanothermobacter thermautotrophicus ΔH DSM 1053 (Mth734), and pMurC (Mfer336), also from M. fervidus were determined to a resolutions of 1.7, 2.7, and 2.5 Å, respectively. The pseudomurein peptide ligase structures share a similar overall three domain arrangement and one shows a rigid-body rotation of the C-terminal domain as observed for murein peptide ligases. The ATP-binding sites in both pMurE and pMurC have been identified based on structure homology. The Nα-UDP-Gluγ-Ala-binding site for pMurE peptide ligase has been proposed based on the UDP-binding position suggesting a similar peptide ligation mechanism as that of MurE peptide ligase. The study thereby suggests a proposed functional role of the pseudomurein peptide ligases and proposes an evolutionary pathway for both murein and pseudomurein peptide ligases from common ancestral genes.
Figure 1.2 re-used with permission.
Keywords: Ligases; Methanobacteriaceae; Archaebacteria